KINETIKA REAKSI HIDROLISIS GULA DARI TETES TEBU MENJADI ASAM OKSALAT - Andaka, Ganjar (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2010)
The kinetics of the hydrolysis of sucrose from molasses have been studied in basic aqueous solutions in the presence of potassium hydroxide. This chemical reaction is to produces oxalic acid as main product. The experiments were conducted in the flask which was completed with stirrer, heater, condenser, and thermometer, at temperatures from 80 to 100oC and at reaction times from 30 to 60 minutes. The product of hydrolysis of molasses was analyzed by using standard solution of potassium permanganate to determine the amount of oxalic acid. The results of these investigations show that the kinetics reaction of the hydrolysis of molasses was found to be first order reaction with respect to sucrose. The reaction rate constant was found to be k = 0,2055 exp(−3367,7663/RT) (in minutes−1) or the activation energy and pre-exponential factor was 3367,7663 cal/gmol and 0,2055 minutes−1, respectively.